Evaluating the Effectiveness of Monetary Policy in Achieving Kaldor Square Balance: An Econometric Study of the Libyan Economy (1990-2024) - Dr. Misbah Mohamed Ghaith (Journal of Scientific and Human Dimensions, 2026)
The aim of this research is to evaluate the effectiveness of monetary policy in the Libyan economy during the period( 1990-2024), through analyzing the ability of money supply-considered the main monetary policy instrument-to achieve the balance dimensions of the Kaldor square, which are economic growth and inflation rate. The results showed that the increase in money supply in the Libyan economy during the study period did not lead to an increase in real GDP; rather, it was associated with a decline in economic growth. The research also found a long-term relationship between money supply and inflation rate, indicating that price pressures in the Libyan economy are directly linked to the expansion of the monetary mass.